A New Cryptographic Key Generation Scheme Using Psychological Signals. (2016) - Akhila, V.A.; Arunvinodh, C.; Reshmi, K.C.; Sakthiprasad, K.M.
Abstract: Ensuring confidentiality and integrity of secret information is the major concern in the field of Biometric Cryptosystems. Security of data transmission is served by the art of encrypted data called cryptography. Biometric cryptography is the emerging methodology in communication networks. Various types of biometrics are available for encryption and also for decryption. This paper introduces a new technique known as brain wave cryptography. Brain waves or signals are generated by the neuron activity of human brain. With the help of sensors brain signals can be captured. After capturing brain waves convert these into digital form. From the brain signals we can generate a secret code or key which can be used as cryptographic key or we can bind key with the help of brain waves. The security of the key can be improved because brain waves will be one of the most powerful biometrics compared to others. This novel approach will enhances the security of the data transmission. This paper also highlights a new idea of automatic ICi selection by taking an average of particular brain regions which resolves the problem of online BCI. The proposed method has been tested in EEG datasets such as .SET, .SMA which succeeds in selecting reference ICi.